Mechanical vapour compression refrigeration system: review part 1: environment challenge - Ahmed Mahmood, Raid; Ali, Omar M.; M. M., Noor (Sciendo, 2020)
In Australia and others developed countries, concerns about global warming have increased, and these concerns influence the use of refrigerants as working fluids in mechanical vapour compression refrigeration systems. One of the most important aspects of refrigerant selection is to reduce its impact on the environment and the ozone layer. This paper provides a comprehensive review of various theoretical and experimental studies which have been carried out on air conditioning and refrigeration applications to investigate the effect of refrigerants on the environment. The analysis in this paper reveals that alternative refrigerants are the most suitable working fluids that can be used in refrigeration systems to meet the needs of the environment. This study also suggests that natural types of refrigerants such as water, carbon dioxide, and hydrocarbon will play a significant role in protecting the environment and providing alternative friendly refrigerants to be used in refrigeration and air conditioning systems.